2021
DOI: 10.1101/2021.10.29.21265663
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and Clinical Profiling of Dysglycemia and HIV infection in Persons with Pulmonary Tuberculosis in Brazil

Abstract: BackgroundThere are scarce data on the prevalence and disease presentation of HIV in patients with tuberculosis (TB) and dysglycemia (diabetes [DM] and prediabetes [PDM]), especially in TB-endemic countries.MethodsWe assessed the baseline epidemiological and clinical characteristics of patients with culture-confirmed pulmonary TB, enrolled in a multicenter prospective cohort in Brazil (RePORT-Brazil) during 2015-2019. Dysglycemia was defined by elevated glycated hemoglobin and stratified as PDM or DM. Addition… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Several studies have demonstrated that TB patients with either HIV or DM have a worse prognosis compared to patients without these co-morbidities, especially when other social or epidemiological factors are present (3,5,8,9). Furthermore, a previous cross-sectional study conducted by our group has demonstrated that TB-HIV patients with DM have higher positive smear and abnormal x-ray rates, as well as more frequent use of alcohol and tobacco when compared to those without DM (10). However, to the best of our knowledge, there have not been any prior studies specifically assessing the effects of concomitant HIV and DM on ATT outcome.…”
Section: Introductionmentioning
confidence: 87%
“…Several studies have demonstrated that TB patients with either HIV or DM have a worse prognosis compared to patients without these co-morbidities, especially when other social or epidemiological factors are present (3,5,8,9). Furthermore, a previous cross-sectional study conducted by our group has demonstrated that TB-HIV patients with DM have higher positive smear and abnormal x-ray rates, as well as more frequent use of alcohol and tobacco when compared to those without DM (10). However, to the best of our knowledge, there have not been any prior studies specifically assessing the effects of concomitant HIV and DM on ATT outcome.…”
Section: Introductionmentioning
confidence: 87%